INFORMATION TECHNOLOGY IN TEACHING AND LEARNING IN EDUCATION - Duraku, Fakete (E-Journal VFU, 2025)
Information technology has now become a key factor in the educational process, and it is changing the teaching as well as the learning methods. This research paper discusses the advantages of technology in vocational schools through curriculum development and the jobs it brings to the students that were from it, focusing on the curriculum plan. The connection of software and vocational schools is plenty, and the put-together will certainly lead to several more job choices in the future of childcare. While the internet and the use of gadgets can be quite good on one side, they could also be the source of problems now and then. This therefore calls for equipping vocational school students with appropriate skills for engagement in modern professions through the use of educational technologies. The information technology setup consequently presents a change in the approach to education delivery and how both the teachers and students achieve professional goals. Its success depends on the establishment of the digital platforms for information consistency with the objectives of education as well as the accessibility of the teaching materials. The 21st-century vocational curriculum has to be adjusted to categorize learners for the fostering of critical thinking, innovation, life, and career skills, applying modern teaching methods. Teachers’ and principals’ professional development is indispensable to integrating those competencies in a practical manner within vocational education. "Integration of Information Technology in Curriculum Planning for Vocational Schools" provides the essence and barriers of information technology integration within vocational education for the Municipality of Prishtina. The present dissertation thesis, based on extensive literature research and prior studies, will be proposing strategies for optimizing curriculum planning with information technology, addressing implications for teaching and the job market. The key to success in vocational education is to have a strong information technology infrastructure that will allow for security and support in teaching and learning. Investments in infrastructure will involve computers, high-speed internet, secure data storage systems, and a variety of other advanced learning applications and platforms.